Altered orbitofrontal and pars opercularis cortical thickness in betel quid dependence chewers - Li Li Fu; Hui Juan Chen; Wei Yuan Huang; Yi Hao Guo; Li Ting Liu; Qing Qing Fu; Hao Dong Qin; Tao Liu; Feng Chen (Therapeutic Advances in Psychopharmacology)
Background: Altered cerebral cortex’s structural organization has been found in individuals with betel quid dependence (BQD). However, the neurological underpinnings of the BQD-related abnormalities in cortical thickness and brain circuitry deficit are largely unknown. Objective: This study aimed to investigate potential abnormalities of brain circuitry in the cortical thickness of BQD individuals by applying the surface-based morphometry (SBM) method. Design: Cross-sectional study. Methods: High spatial resolution, three-dimensional T1-weighted structural imaging data were collected from 53 individuals with BQD and 37 healthy controls (HCs) who were similar to the BQD group in terms of age, sex, and educational level. The SBM method was applied to analyze the cortical thickness alterations in BQD-related areas. Independent-samples t -test was used to assess the cortical thickness difference between the two groups. Pearson correlation analysis was used to investigate the correlation between cortical thickness changes and clinical characteristics, including BQD scale scores and duration of BQD. Results: The BQD group had a higher cortical thickness than the HC group at the lateral orbitofrontal ( t = 4.703, p = 0.0028) and pars opercularis ( t = 3.602, p = 0.0403) clusters in the right cerebral hemisphere, with age, sex, and education duration as covariates ( p < 0.05, Monte Carlo). There were no significant differences in age, sex, or education duration-adjusted cortical thickness of the left cerebral hemisphere between BQD chewers and HCs ( p > 0.05, Monte Carlo). Correlation analysis revealed that the cortical thickness of the right pars opercularis was negatively correlated with the BQD duration ( r = −0.274, p = 0.047). The cortical thickness of the right lateral orbitofrontal cluster was not significantly correlated with Betel Quid Dependence Scale (BQDS) or BQD duration ( p > 0.05). Conclusion: This study demonstrated that BQD might be associated with changes in the orbitofrontal and pars opercularis cortical thickness, which may be related to the neurobiological basis of BQD.